Evaluation of ImpediMed SFB7 BIS device for low-impedance measurements. (December 2018) - Freeborn, Todd J.; Milligan, Ashley; Esco, Michael R.
Highlights: SFB7 device is 1% accurate down to 10  Ω for frequencies to 100 kHz. SFB7 device is 5% accurate down to 10  Ω for frequencies to 1 MHz. Variability insensitive to temperature in the range from 10 °C to 35 °C. High frequency SFB7 measurements have significant inductive component. Abstract: The SFB7 bioimpedance spectroscopy (BIS) device from ImpediMed is a widely utilized tool for clinical research in a variety of applications, marketed for the estimation of body composition in individuals. This device has a rated accuracy of 1 % for measurements from 50  Ω to 1 k Ω from 3 kHz to 1 MHz, making it an ideal choice for the measurement of full-body impedance. Recent research has also used this device to collect impedance measurements from localized regions of tissue which in some cases may be below the 50  Ω rated value. In this work, the measurements of impedances below 50  Ω are compared to measurements collected from a Keysight E4990A impedance analyzer in this low impedance range. Concluding that the SFB7 device is 1 % accurate for resistance measurements as low as 10  Ω for frequencies below 100 kHz and 5 % accurate for frequencies to 1 MHz. While 1  Ω measurements are possible, their much higher variability decrease their expected accuracy to approximately 5 % for frequencies below 100 kHz and 30 % for frequencies up to 1 MHz.